THE STUDY RESULTS OF MORPHO-BIOLOGICAL TRAITS OF NORTH AMERICAN ALFALFA SAMPLES - S. A. Ignatiev; А. А. Regidin; T. V. Grayzeva; K. N. Goryunov (Зерновое хозяйство России, 2019)
Alfalfa is the most valuable forage crop spread all over the world. Due to the varietal diversity of alfalfa in the countries of North America, the laboratory of breeding and seed-growing of perennial grasses of the FSBSI “Agricultural Research Center “Donskoy” conducted the experiments over 27 samples of American and Canadian breeding to find genetic sources of economic and biological traits. The field trials were conducted according to generally accepted methods for forage crops in 2016–2018. The area of experimental plots was 1 m2 with double sequence. The period “beginning of spring germination” and “beginning of flowering” were studied depending on the climatic conditions of the year. In 2016 and 2017 spring germination took place in March, and in 2018 it was in the 1-st decade of April. Beginning of flowering in the studied samples ranged from the 3-d decade of May to the 1-st decade of June. On average, over 3 years, the number of days in the period “beginning of spring germination – beginning of flowering” varied from 68 to 73 days. This period of the standard variety was 72 days. The studied samples had this period on 1–4 days shorter, excluding the samples “K-33299” and “K-42249” (73 days). According to the yield of green mass, none of the samples reliably exceeded the standard variety “Rostovskaya 90” (3.29 kg/m2). The studied alfalfa samples formed 1.57–3.5 kg/m2 of green mass. According to the plant foliage amount, the indicators of the studied samples varied from 42 to 49%. The samples “K-33299” and “K-43272” with 49% of foliage amount slightly exceeded the standard variety “Rostovskaya 90” (48%). The hay yield of the studied samples varied from 31 to 40%, “K-43272” formed the smallest indicator (31%), “K-42249” and “K-45715” (40%) produced the largest amount and when the hay productivity of the standard variety was 35%. There have been identified reliable correlations between the yield of green mass and hay, as well as between the yield of green mass and the number of days during the period “beginning of spring germination – beginning of flowering”.